2011
DOI: 10.1590/s0102-79722011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Validação da Escala de Abordagens de Aprendizagem (EABAP) em uma amostra brasileira

Abstract: Resumo O presente estudo teve como objetivo validar a Escala de Abordagens de Aprendizagem (EABAP), construída para mensurar a dimensão Superficial e Profunda, em uma amostra brasileira. Fizeram parte da pesquisa 716 estudantes do ensino fundamental e médio de uma escola de Belo Horizonte. A análise fatorial exploratória foi utilizada para a identificação das dimensões e seleção dos melhores itens. Dos 27 itens estipulados, foram mantidos 17. A Análise Fatorial Confirmatória indicou a adequação da solução de u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…The theory assumes that students have two basic ways of approaching objects of knowledge, a deep one, using high-order cognitive processes and intrinsic motivations, and a superficial one, using loworder cognitive processes and extrinsic motivations (Gomes & Linhares, 2018). Gomes, 2010aGomes, , 2010bGomes, , 2011bGomes, , 2012bGomes & Borges, 2009b, 2009cGomes et al, 2014aGomes et al, , 2014cGomes & Golino, 2012a, 2012c BAFACALO's tests , 2021b The field which studies approaches has brought important contributions to students' learning approaches, as well as the relationship between teaching, in its different forms, and learning (Gomes, 2010c(Gomes, , 2011a(Gomes, , 20132022b;Gomes & Golino, 2012c;Gomes & Linhares, 2018;Gomes et al, 2011Gomes et al, , 2020bRodrigues & Gomes, 2020). Evidence has shown that the deep and surface approaches are reasonable predictors of academic performance, with similar predictions to other psychoeducational variables related to motivation, beliefs, and conceptions, despite being secondary predictors if compared to intelligence or metacognition (Table II).…”
Section: Presentation Of the Approach-in-process Test (Version 2)mentioning
confidence: 99%
“…The theory assumes that students have two basic ways of approaching objects of knowledge, a deep one, using high-order cognitive processes and intrinsic motivations, and a superficial one, using loworder cognitive processes and extrinsic motivations (Gomes & Linhares, 2018). Gomes, 2010aGomes, , 2010bGomes, , 2011bGomes, , 2012bGomes & Borges, 2009b, 2009cGomes et al, 2014aGomes et al, , 2014cGomes & Golino, 2012a, 2012c BAFACALO's tests , 2021b The field which studies approaches has brought important contributions to students' learning approaches, as well as the relationship between teaching, in its different forms, and learning (Gomes, 2010c(Gomes, , 2011a(Gomes, , 20132022b;Gomes & Golino, 2012c;Gomes & Linhares, 2018;Gomes et al, 2011Gomes et al, , 2020bRodrigues & Gomes, 2020). Evidence has shown that the deep and surface approaches are reasonable predictors of academic performance, with similar predictions to other psychoeducational variables related to motivation, beliefs, and conceptions, despite being secondary predictors if compared to intelligence or metacognition (Table II).…”
Section: Presentation Of the Approach-in-process Test (Version 2)mentioning
confidence: 99%
“…Quanto à relevância das pesquisas sobre abordagens à aprendizagem, há evidências de que a utilização da AP influencia positivamente o desempenho acadêmico, contribui para uma aprendizagem efetiva, possibilita a superação de dificuldades pessoais e ambientais, e potencializa a aprendizagem (DA SILVA e SÁ, 1993;GARNER et al, 1984;GOMES, 2011;PRESSLEY e LEVIN, 1983).…”
Section: Abordagens à Aprendizagemunclassified
“…The Brazilian Learning Approaches' Scale is a self-report questionnaire composed by 17 items, developed by Gomes and colleagues (Gomes, 2010;Gomes, Golino, Pinheiro, Miranda, & Soares, 2011). Nine items were elaborated to measure deep learning approaches, and eight items measure surface learning approaches.…”
Section: Participantsmentioning
confidence: 99%
“…BLAS presents reliability, factorial structure validity, predictive validity and incremental validity as good marker of learning approaches. These psychometrical proprieties are described respectively in Gomes (2010Gomes ( , 2011 and Gomes et al (2011). The DAP and SAP's factor scores are used in the current study.…”
Section: Participantsmentioning
confidence: 99%